Nilai-Nilai Kearifan Lokal yang Terdapat pada Bagas Godang di Desa Pidoli Dolok Kecamatan Panyabungan Kota Kabupaten Mandailing Natal - Dirham Pasaribu; Jekmen Sinulingga (Journal of Social Interactions and Humanities, 2022)
This study aims to explain and discover about the values ​​of local wisdom of the Mandailing ethnicity, the function of symbols and to describe the value of symbols. In this study the method used in analyzing the problem is a qualitative method. This study uses the theory According to Danesi and Perron. There have been so many changes that have happened to the House or Bagas Godang because of the progress of the times.